SIFAT LISTRIK MEMBRAN SELULOSA ASETAT - TITANIUM DIOKSIDA - Jajang Juansah (Jurnal Biofisika, 2012)
Membrane  is  a  semiperiable  tissue.  Now  days,  the  technology  of  membrane  is commonly  used  for  separation  process.  Research  membrane  filtration  process  is mostly done,  but  the  investigations of their  electrical properties are  rarely  performed. Electrical  properties  of  membrane  were  investigated  by  using  measurement  of current-voltage, capacitance, and impedance phenomenon at low alternating current. The  more  value  of  frequency  of  signal,  the  more  of  conductance  value.  The capacitance  and  impedance  were  decreased   If  frequency  was  inclined.  The  TiO2 addition  in  cellulose  membrane  couse  the  electrical  properties  of  membrane changes.  It  was  happen  until  optimum  value  TiO2.  The  differences  in  electrical parameters was shaw clearly in the range of 10 Hz to 1 kHz.